Microencapsulation preservation of the stability and efficacy of Citrus grandis oil-based repellent formulation against Aedes aegypti during storage - Misni, Norashiqin; Mohamed Nor, Zurainee; Ahmad, Rohani; Ithnin, Nur Raihana; Unyah, Ngah Zasmy (MDPI, 2021)
Essential oils have been widely used as an active ingredient in mosquito repellent products. However, essential oils are highly unstable and prone to degradation when exposed to the environment during storage. Microencapsulation techniques help to maintain the stability of molecules in essential oils that are sensitive to environmental stress, and therefore improve shelf life. In this study, the physical stability and efficacy of a repellent formulation consisting of encapsulated Citrus grandis essential oil (CGEO) were evaluated under different storage conditions over a 12-month period by comparing the formulation with a non-encapsulated formulation. The formulations were both stored under two different storage conditions, i.e., 25 ± 2 °C/60% ± 5% relative humidity (RH) and 40 ± 2 °C/75% RH ± 5%, for 12 months. Droplet size, zeta potential, and pH value were measured after 1, 6, and 12 months of storage to determine their stability. For the study of efficacy, each formulation was tested against Aedes aegypti under laboratory conditions. We found that the microencapsulated formulation’s physical characteristics showed insignificant changes as compared with the non-encapsulated formulation during storage. The microencapsulated formulation demonstrated better repellent effects, sustaining high protection (>80%) for 4 more hours of exposure after 12 months of storage as compared with the non-encapsulated formulation that demonstrated high protection for only an hour post application. Microencapsulation helped to preserve the stability of the formulation, which resulted in high protection being maintained for over 12 months of storage.